2017
DOI: 10.4103/ijmr.ijmr_1319_15
|View full text |Cite
|
Sign up to set email alerts
|

Study of stem cell homing & self-renewal marker gene profile of ex vivo expanded human CD34+ cells manipulated with a mixture of cytokines & stromal cell-derived factor 1

Abstract: Background & objectives:Next generation transplantation medicine aims to develop stimulating cocktail for increased ex vivo expansion of primitive hematopoietic stem and progenitor cells (HSPC). The present study was done to evaluate the cocktail GF (Thrombopoietin + Stem Cell factor + Flt3-ligand) and homing-defining molecule Stromal cell-derived factor 1 (SDF1) for HSPC ex vivo expansion.Methods:Peripheral blood stem cell (n=74) harvests were analysed for CD34hi CD45lo HSPC. Immunomagnetically enriched HSPC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…To test stem cell implantation ability, Liang et al [28] injected young or old BM cells into congenic mice, and they found that the homing efficiency of old mouse was approximately three-fold lower than that of young mouse. Some specific genes have been demonstrated to be crucial in regulating HSC repopulation, such as Cdc42, Ccr9, Gnrh2, and Lep [29,30]. CD44 is critical in the maintenance and migration of HSCs [31], and the absence of CD44 in neonatal BM was shown to enhance the longterm engraftment potential of HSCs.…”
Section: Homing and Engraftmentmentioning
confidence: 99%
“…To test stem cell implantation ability, Liang et al [28] injected young or old BM cells into congenic mice, and they found that the homing efficiency of old mouse was approximately three-fold lower than that of young mouse. Some specific genes have been demonstrated to be crucial in regulating HSC repopulation, such as Cdc42, Ccr9, Gnrh2, and Lep [29,30]. CD44 is critical in the maintenance and migration of HSCs [31], and the absence of CD44 in neonatal BM was shown to enhance the longterm engraftment potential of HSCs.…”
Section: Homing and Engraftmentmentioning
confidence: 99%
“…In contrast, hCXCL12 Q48K displayed a slower release, demonstrating a stronger heparin binding. This variant remained longer in the hydrogel compared to wild type hCXCL12, where it could serve as a homing factor for the recruited stem and progenitor cells before its delayed release. , …”
Section: Discussionmentioning
confidence: 90%
“…This variant remained longer in the hydrogel compared to wild type hCXCL12, where it could serve as a homing factor for the recruited stem and progenitor cells before its delayed release. 51,52 To test whether progenitor cells, which are addressed in vivo, would react to the loaded hydrogels, we used eEPCs in migration studies. We found a significantly higher migration effect of the gels loaded with the low-affinity K24/K27/R41/ R47A mutant.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Overcoming this limitation, several studies have been done to find the best strategies for UCB‐HSC expansion over the last decades. Almost all strategies have a general consensus to use recombinant human (rhu) growth factors such as stem cell factor (SCF), thrombopoietin (TPO), and fms‐like tyrosine kinase 3 ligand (Flt3L) …”
Section: Introductionmentioning
confidence: 99%
“…Almost all strategies have a general consensus to use recombinant human (rhu) growth factors such as stem cell factor (SCF), thrombopoietin (TPO), and fms-like tyrosine kinase 3 ligand (Flt3L). 1 CD34 + HSC/MSC coculture system in presence of ex vivo growth factors is increasingly being used as a method for UCB-HSC expansion. 2 It can mimic the bone marrow HSC niche.…”
Section: Introductionmentioning
confidence: 99%